Pharmacogenetic prediction of clinical outcome in advanced colorectal cancer patients receiving oxaliplatin/5-fluorouracil as first-line chemotherapy - Paré, L (Nature Publishing Group, 2008)
To determine whether molecular parameters could be partly responsible for resistance or sensitivity to oxaliplatin (OX)-based chemotherapy used as first-line treatment in advanced colorectal cancer (CRC). We studied the usefulness of the excision repair cross-complementing 1 (ERCC1), xeroderma pigmentosum group D (XPD), XRCC1 and GSTP1 polymorphisms as predictors of clinical outcome in these patients. We treated 126 CRC patients with a first-line OX/5-fluorouracil chemotherapeutic regimen. Genetic polymorphisms were determined by real-time PCR on an ABI PRISM 7000, using DNA from peripheral blood. Clinical response (CR), progression-free survival (PFS) and overall survival (OS) were evaluated according to each genotype. In the univariate analysis for CR, ERCC1-118 and XPD 751 polymorphisms were significant (P=0.02 and P=0.05, respectively). After adjustment for the most relevant clinical variables, only ERCC1-118 retained significance (P=0.008). In the univariate analysis for PFS, ERCC1-118 and XPD 751 were significant (P=0.003 and P=0.009, respectively). In the multivariant analysis, only the XPD 751 was significant for PFS (P=0.02). Finally, ERCC1-118 and XPD 751 polymorphisms were significant in the univariate analysis for OS (P=0.006 and P=0.015, respectively). Both genetic variables remained significant in the multivariate Cox survival analysis (P=0.022 and P=0.03). Our data support the hypothesis that enhanced DNA repair diminishes the benefit of platinum-based treatments.